Growth patterns of captive painted terrapins Batagur borneoensis in the Aceh Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mawardi AL, Atmaja THW, Sarjani TM, Khalil M, Sarong MA, Yusriono. 2022. Growth patterns of captive painted terrapins Batagur borneoensis in the Aceh Province, Indonesia. Biodiversitas 23: 4872-4878. Painted terrapin is one of the endemic animal species found only in Indonesia and Malaysia. These animals live in very wide waters, which include rivers, mangroves and coastal areas. The purpose of this study was to determine the growth pattern of Batagur borneoensis at the Marine Tuntong Education and Conservation Center, Satucita Lestari Indonesia Foundation, Aceh Province. The study used a survey method with data collection techniques by direct observation to the location of the captive B. borneoensis to obtain comprehensive data. The sample used in this study was the captive-bred B. borneoensis at the Marine Tuntong Education and Conservation Center Satucita Lestari Indonesia Foundation with different age variations, including 2 months, 2 years, 3 years and 4 years, with a total sample 3 individuals per age category. Parameters measured in this study included the total weight of B. borneoensis, carapace arch length and carapace arch width. In general, the growth pattern of B. borneoensis found in the education and conservation center at YSCLI is classified as negative allometric, this growth indicates that length growth is faster than overall body weight gain. When viewed based on the age difference, the growth pattern of B. borneoensis aged 2 months to 2 years is still classified as positive allometric, but when it is 3 to 4 years old, it only changes to negative allometric. It can be concluded that for the age of 2 years and under, the captive process of B. borneoensis is still suitable, but when it is over 2 years old, it is no longer suitable for captivity, considering that the animal's growth pattern is not balanced between carapace length and total body weight. It is recommended that if the animal is over 2 years old, it should be immediately released into its natural habitat in the wild so that it can live and develop naturally in order to preserve the aquatic biota.
Keywords: Captivity policy, conservation, endangered species